Developing a national code of ethics for pharmacists in Kuwait: Insights from a survey and a modified Delphi study - Salah Waheedi; Razan Alfailakawi; Shuaa Al-Selili; Hawraa Ghadanfari; Asmaa Al-Haqan (PLoS ONE, 2025)
Background Pharmacists play a crucial role in healthcare and are expected to uphold high ethical standards. Establishing a code of ethics for pharmacists is essential as it supports improved patient outcomes and increases trust in the healthcare system. Regulatory organizations worldwide have recognized the significance of such codes in guiding professional behaviour and ensuring quality care. However, a national code of ethics for pharmacists in Kuwait has not yet been published. The aim of this study was to propose a national code of ethics for pharmacists in Kuwait, using insights from a survey of practicing pharmacists and a modified Delphi study involving expert consensus. Methods A mixed methodology was employed comprising a survey of practicing pharmacists to gather their views on the clarity and acceptance of the 14 FIP standards and a modified Delphi study involving a group of experts to finalize and formulate the national code of ethics for pharmacists in Kuwait. For the survey, all registered pharmacists practicing in Kuwait were invited to participate through the Kuwait Pharmaceutical Association. Data collection occurred between February and May 2019 via an electronic questionnaire. The Delphi study participants were recruited through purposive and snowball sampling, with data collection taking place between March and June 2023. The Delphi study required a 90% consensus threshold for standard inclusion. Results A total of 304 pharmacists (7.6% response rate) participated in the survey. The median age was 32 years, with a gender distribution of 56.6% female. The majority (85%) reported Arabic as their first language, and 75% held a BPharm degree. Most participants found the standards clear and acceptable, with clarity percentages generally above 88% and acceptance percentages similarly high. Standards 3 (patient autonomy) and 11 (competency of support staff) had slightly lower ratings, indicating potential areas for improvement. Comments highlighted issues such as patient knowledge and the clarity of support staff roles. In the Delphi study, 30 experts participated in the first round, with standards needing a 90% consensus for inclusion. Seven standards reached consensus in the first round, four in the second, and four in the third. Standard 11 failed to achieve consensus and was removed. The iterative process ensured thorough evaluation and refinement of each standard based on expert feedback. Conclusion This study proposed a national code of ethics for pharmacists in Kuwait based on a comprehensive mixed-methods approach. The survey indicated high clarity and acceptance of most FIP standards among pharmacists, though areas for improvement were identified. The Delphi study achieved consensus on 13 out of 14 standards. This proposal provides a foundation for regulators to establish a formal code of ethics, aiming to enhance professionalism and patient trust in the healthcare system.